The The Effect of Using Chain Story Technique In Writing Descriptive Text For The Grade Students of SMP Negeri 14 Medan - Pakpahan, Yohana Serepina (The Explora, 2021)
The study focused on finding out the effect of applying Chain Story Technique in writing descriptive text. The chain story technique is a technique which is used to make writing class more interesting. this technique is suitable use in writing activity. It can help teacher in teaching learning process and can help students to understand quickly to make summary of the text. The population of the research was the eight grade students of SMP NEGERI 14 MEDAN. There were fourty eight students of the eight grade as the sample of the research. This study was conducted with two randomized class namely experimental class and control class. The experimental class was taught by applying Chain Story Technique, while the control class was taught without Chain Story Technique. The instrument of collecting the data was writing test. The data were analyzed by using reliability (KR21) and t-test formula. The calculation shown that the mean score of students in experimental class is 8,45 and the mean score of control class who are taught without Chain Story technique is 3,25. It can be concluded that the mean score of experimental class is higher than control class. There is a significant difference scores between experimental group and control group. Based on research finding, it is concluded that t-observed is higher than t-table. T-obs> t- table (p=0.05) 8.813>1.679. it means that H0 is rejected and Ha is accepted. Chain Story Technique significantly affects on the eight grade students of SMP NEGERI 14 MEDAN in writing descriptive text. It is suggested the English Department Students, lecturer and all of people to use this strategy